Colonization of decomposing Sphagnum moss litter by mycorrhizal roots in two types of peatland ecosystems - Wilk, Mateusz; Pawłowska, Julia; Wrzosek, Marta; Gorczak, Michał; Suska-Malawska, Małgorzata (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
During a 35-month study on the decomposition of Sphagnum moss litter in poor fen and pine bog forest, an intensive colonization of litter-bags by mycorrhizal roots was observed during the decomposition process. Content of mycorrhizal roots in litter-bags, expressed as % mass of roots, was generally increasing during the decomposition in pine bog forest, and fluctuating during decomposition on poor fen, although in both cases the results were statistically insignificant. Two morphotypes of ericoid roots and two morphotypes of ectomycorrhizal roots were recorded from litter-bags on poor fen during the decomposition experiment, while in pine bog forest one morphotype of ericoid and nine morphotypes of ectomycorrhizal roots were recorded. Molecular identification of mycorrhizal roots succeeded only in the case of one ericoid and six putatively ectomycorrhizal morphotypes. Most morphotypes were recorded only once during the whole 35-month decomposition period, and only one ericoid and one ectomycorrhizal morphotypes were shared between the poor fen and pine bog forest communities.